Analysis of pulsed electric field effects on cellular tissue with Cole–Cole model: Monitoring permeabilization under inhomogeneous electrical field with bioimpedance parameter variations. (May 2015) - Trainito, C.I.; Français, O.; Le Pioufle, B.
Abstract: Cell electropermeabilization, which is induced by the application of a pulsed electrical field (PEF), temporarily facilitates the passage of various macromolecules through the membrane. The degree of permeabilization of a cell tissue depends on the characteristics of the applied PEF, and can be characterized by the evolution of its bioimpedance. This paper presents an approach to quantify and analyze changes induced by various characteristics of PEF applied by a simple pair of metal needles inserted in a vegetal tissue, using the bioimpedance monitoring. The dependence of the Cole-Cole model with the level of permeabilization is examined and discussed. In the context of the defined protocol for PEF application, this work shows that the degree of permeabilization of a tissue can be characterized not only by the resistive part of the bioimpedance model, but also by its capacitive part, particularly in the case of a low level of permeabilization. Industrial relevance: Nowadays cell tissue electropermeabilization is broadly used in food industry for the improvement of juice production, the enhancement of compound extraction from vegetables, etc.. Nevertheless, a better knowledge of both the dynamics of the permeabilization process and the elements that significantly influence the degree of permeabilization would be extremely important in the perspective of optimization of both extraction and production. This paper compares the effects of PEF characteristics on tissue permeabilization and their efficiency to achieve a desired degree of permeabilization. Highlights: Biological and electrochemical contributions of the impedance spectrum are separated. Cole–Cole components are estimated in the case of inhomogeneous field. The tissue permeabilization is observed in relation with electrical pulse characteristics. Permeabilization level is linked to resistive and capacitive impedance components.